Susceptibility and morbidity between male and female Swiss mice infected with Angiostrongylus costaricensis: Susceptibilidade e morbidade entre camundongos Swiss machos e fêmeas infectados com Angiostrongylus costaricensis - Márcia B. Mentz; Eliane Dallegrave; Carlos Graeff-Teixeira (Revista do Instituto de Medicina Tropical de São Paulo, 2010)
The gender of vertebrate hosts may affect the outcome of parasitic infections. An experimental murine infection with Angiostrongylus costaricensis was followed with determinations of body weight, fecal larval elimination, number and length of adult worms, number of macroscopic intestinal lesions, and mortality. Groups of male and female Swiss mice were infected with 10 3rd-stage A. costaricensis larvae per animal. The results indicate there are no significant differences related to gender of the host, except for higher length of worms developed in male mice. O sexo dos hospedeiros vertebrados pode influenciar no resultado de infecções parasitárias. A infecção experimental de camundongos com Angiostrongylus costaricensis foi acompanhada com observação do peso corporal, eliminação de larvas nas fezes, número e comprimento dos vermes adultos, número de lesões macroscópicas nos intestinos e mortalidade. Grupos de camundongos Swiss machos e fêmeas foram infectados cada um com 10 larvas de terceiro estágio de A. costaricensis. Os resultados indicam que não há diferenças significativas relacionados ao sexo dos hospedeiros, exceto pelo maior comprimento dos vermes nos hospedeiros machos.